Response of LQ45 Stock Market on Indonesia Legislative and Presidential Election Result in 2019 - Siti Rahmani Frihartina; Mursidi Mursidi; Dewi Nurjannah (Universitas Muhammadiyah Malang, 2021)
The purpose of this study was to determine the response of LQ45 stock market participants to the legislative and presidential elections and the results of the 2019 presidential election. The data used to determine the response of market participants is to use abnormal return data and trading volume activity from 45 companies listed on LQ45. The test is then calculated using the marked adjusted model method and testing the hypothesis using parametric statistics and analyzed using SPSS. Based on the results of research conducted, it can be concluded that for the legislative and presidential election events, in 2019 there were significant abnormal return differences and for trading volume activity there were no significant differences around the day the event occurred. The second political event, namely the results of the presidential election, the calculation of abnormal returns and trading volume activity around the day of the event was found to be a significant difference in which this event there was a response from the stock market players which means that both hypotheses in this study were accepted in this second political event.